Smoking and hepatocellular carcinoma mortality - SIEGEL, ABBY B. (D.A. Spandidos, 2012)
The association between cigarette smoking and mortality from hepatocellular carcinoma (HCC) is ambiguous. We analyzed the association between smoking and mortality in HCC patients seen at our center. We collected data retrospectively on patients diagnosed with HCC between 2002 and 2009. We estimated the association of smoking history with demographic, clinical and treatment factors. We then modeled these factors as predictors of mortality. Among smokers, we analyzed the effects of pack-year history and cessation times on survival. Two hundred and twenty-three out of 444 patients with HCC had a history of smoking. Smokers were more likely to be younger at diagnosis, to have α fetoprotein (AFP) values less than the median, and to have had surgery (p=0.04) compared to non-smokers. In a Cox model, younger age, lower AFP and Child's Class were all independently predictive of survival, but smoking was not. Smokers with over 20 pack-years did not have worse survival than lighter smokers, and cessation times also did not affect survival after controlling for age. We found a significant interaction between smoking and drinking. In our data, smoking was not independently associated with HCC survival in a multivariable model. Smoking was associated with favorable prognostic features which likely outweighed any independent effect of smoking.